Dynamics of liquid slug using particle image velocimetry technique - Siddiqui, M.I. (American Institute of Physics Inc., 2016)
Two phase liquid-gas slug flow is a source of vibration and fatigue on pipe walls and downstream equipment. This paper examines the effect of inlet conditions on the stream-wise velocity profiles and on the shear stresses induced by the liquid phase on the pipe wall during the slug flow. Instantaneous velocity vector fields of the liquid-gas (water-air) slug flow regime were obtained using particle image velocimetry (PIV) technique at various inlet conditions. A 6-m long Plexiglas pipe having an internal diameter 74-mm with a slight inclination of about 1.16Â°was considered for the visualization of the flow pattern. Test section was employed at a point 3.5m from the inlet, mounted with optical correction box filled with water to minimize the curvature effect of pipe on the PIV snapshots. Stream-wise velocity profiles are obtained at the wake of the liquid slug and the effect of inlet conditions were analyzed. A direct relationship was observed in between superficial gas velocity and the liquid stream-wise velocity at wake section of the slug flow. Further, the lower wall shear stresses were obtained using PIV velocity profiles at liquid film and the slug wake sections in a unit slug. The wall shear stress remained higher in the liquid slugy body as compared to the liquid film. Moreover, an increase in the wall shear stress was observed by increasing the gas superficial velocities. Â© 2016 Author(s).